Alirocumab post-acute coronary syndrome: An integrative review on treatment and its influence on future cardiovascular and metabolic complications (Research, Society and Development, 2025)
Acute Coronary Syndrome (ACS) is a serious condition resulting from obstruction of blood flow in the coronary arteries and it is one of the main causes of cardiovascular morbidity and mortality, especially among adults and the elderly, in whom non-traditional risk factors are more prevalent. This integrative review article aims to explore the clinical characteristics, specific risk factors, and related health outcomes after ACS in treatment with Alirocumab to offer a broad and well-founded view on the subject, directing new perspectives for improving the treatment and control of symptoms and recurrences. The review selected articles published between 2020 and 2024 in the PubMed, Scielo, and Google Scholar databases. The results show that alirocumab significantly reduces LDL-C, lipoprotein(a), and apoB levels, reducing the risk of major cardiovascular events (MACE) by up to 15%. Furthermore, the benefits were more pronounced in patients with multiple metabolic risk factors. The discussion reinforces the importance of more rigorous lipid management goals and suggests that alirocumab can be integrated into personalized therapeutic strategies, especially for patients with higher residual cardiovascular risk. It is concluded that alirocumab plays a central role in post-ACS management, standing out for its multidimensional approach and the potential to reduce cardiovascular complications in diverse populations.